A new ZIF molecular-sieving membrane for high-efficiency dye removal. Issue 24 (6th March 2019) - Li, Zhan; Yang, Pingping; Gao, Zhuangzhuang; Song, Mingqiu; Fang, Qianrong; Xue, Ming; Qiu, Shilun
Abstract : A new and robust ZIF membrane was prepared and demonstrated excellent dye removal capacity due to its unique pore structure. Abstract : A new and robust ZIF membrane was successfully prepared and evaluated for dye removal capacity. Benefitting from its favourable pore structure and thin selective layer, this ZIF membrane showed excellent removal efficiency for a variety of dyes, with rejection rates of over 99.8% and high water flux up to ∼100 L m −2 h −1 .